Coffee Peel Waste Utilization Planning: A Causal Loop Analysis - Januardi; Febby Pangestu Iskandar; Devi Rahmah (Fakultas Rekayasa dan Teknologi Industri, 2024)
The rise of green bean coffee production in Bandung has significantly shaped the city's coffee landscape, with Bandung producing more than 30% of West Java's total coffee production. However, this growth brings a pressing challenge: managing the waste generated during green bean coffee processing, particularly remnants from pulping. This research explores ways to utilize coffee peel waste into profitable products in Bandung through a Causal Loop Analysis. Primary and secondary data are used to compile the conceptual model of coffee peel waste using STELLA Software. The model includes a basic model, a fertilizer model, and a bio pellet model. The analysis highlights potential reductions in waste management costs and the environmental benefits of converting organic waste into fertilizer and bio pellets. Fertilizer is chosen for its ease of implementation and low production costs, while bio pellets are valued for their superior energy characteristics and high-value chemical compounds. The study also examines revenue sharing mechanisms among stakeholders, suggesting equitable distribution models to ensure fair economic benefits across the supply chain, including farmers and industry.